1998
DOI: 10.1111/j.1524-4725.1998.tb04147.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma in a Patient with Chronic Lymphocytic Leukemia

Abstract: CLL is a malignancy that primarily effects the elderly population and markedly increases their risk of developing skin cancers, especially SCC. An intense infiltrate may be present surrounding the tumor. This case report demonstrates one of the potential challenges the Mohs surgeon may face in interpreting histologic frozen section. Immunohistochemistry may be helpful in providing a more definitive answer to this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Five of the 6 nontransplant recipients in this series had tumors classified as high‐risk SCC by Rowe et al 2 including large and/or recurrent tumor. One patient in the nontransplant group had a history of CLL which has been associated with aggressive SCC 10–13 …”
Section: Discussionmentioning
confidence: 99%
“…Five of the 6 nontransplant recipients in this series had tumors classified as high‐risk SCC by Rowe et al 2 including large and/or recurrent tumor. One patient in the nontransplant group had a history of CLL which has been associated with aggressive SCC 10–13 …”
Section: Discussionmentioning
confidence: 99%
“…Frierson et al 4 and Perez‐Reyes and Farhi 5 reported metastatic disease in 33% to 50% of patients with CLL and SCC. Because of the potential for recurrence and metastasis, management of these cutaneous tumors with microscopically controlled margins is recommended 10,11 …”
Section: Discussionmentioning
confidence: 99%
“…Because of the potential for recurrence and metastasis, management of these cutaneous tumors with microscopically controlled margins is recommended. 10,11 Cutaneous infiltrates of CLL in association with primary cutaneous malignancies have been described.…”
Section: Discussionmentioning
confidence: 99%
“…For surgeons who perform the Mohs operation, dense lymphocytic infiltrates associated with non‐melanoma skin cancers may pose an intraoperative challenge for interpretation of histologic sections because they obscure possible residual tumor. If the infiltrate represents inflammation caused by tumor, then further resection may be indicated, whereas leukemic infiltrates that do not imply tumor would not require further resection 7 . Leukemic infiltrates also complicate the pathologic findings by camouflaging tumor cells or trapping collagen in a manner that disguises tumor islands.…”
mentioning
confidence: 99%